1997
DOI: 10.1007/s11745-997-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid metabolism in young‐old parabiotic rats

Abstract: Serum cholesterol, triglyceride and phospholipid levels, liver cholesterol concentration, bile flow, biliary cholesterol, phospholipid and bile acid secretion rates, fecal sterol and bile acid levels and their bile acid compositions were examined in young-old parabiotic rats and compared with those in young and old control rats and young-young parabiotic rats. Bile acid composition was expressed in terms of the cholic acid group/chenodeoxycholic acid group (CA/CDCA) ratio. Body weight (BW) gain decreased after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Just as human subjects can be randomly paired with flatmates to share the same dormitory environment, animal subjects have been paired with other animals to share a circulatory system. Parabiosis has been used to study a range of health outcomes, including tumour growth , cholesterol and diabetes . Parabiosis experiments helped lay the foundation for the discovery of leptin after work by Coleman suggested that a satiety factor found in db/db mice but not ob/ob mice could regulate appetite.…”
Section: Examples Of Presmentioning
confidence: 99%
“…Just as human subjects can be randomly paired with flatmates to share the same dormitory environment, animal subjects have been paired with other animals to share a circulatory system. Parabiosis has been used to study a range of health outcomes, including tumour growth , cholesterol and diabetes . Parabiosis experiments helped lay the foundation for the discovery of leptin after work by Coleman suggested that a satiety factor found in db/db mice but not ob/ob mice could regulate appetite.…”
Section: Examples Of Presmentioning
confidence: 99%
“…Cross circulation is a technique in which two animals share a common circulation. This technique is applied in fundamental research, such as immunological analysis of immune cell migration, 1,2 supply of stem cells in bone marrow diseases, 3,4 and dialysis of blood toxin in toxic diseases caused by liver 5,6 or renal dysfunctions. 7 In the past, this technique was used in clinical treatment of hepatic insufficiency, 8 uremia, 9 nephrotic syndrome, 9 and malignant hypertension 9 ; however, it is not currently performed due to infections and serum shock among incompatible pairs.…”
Section: Microsurgery 20:116-120 2000mentioning
confidence: 99%
“…Even at the most "dan ger ous zone" -the im mu nity. How ever, the later works stated the fa vour able con se quences for the old an i mal in the parabiotic sys tem with the young one [9,10]. The au thors do not dis cuss the rea sons for di ver sity of such re sults.…”
mentioning
confidence: 98%